PERCEIVED EXTERNAL PRESTIGE ON DEVIANT WORKPLACE BEHAVIOR WITH MEDIATION OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Pratiwi, Ita Wahyu; Armanu, Armanu; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2022)
This study focuses on perceived external prestige in reducing deviant workplace behavior by mediating job satisfaction and organizational commitment. This study aimed to determine and analyze the effect of perceived external prestige on deviant workplace behavior, either directly or indirectly, through the mediation of job satisfaction and organizational commitment. This study used saturated sampling. The sample used in this study is the civil servant of the Regional Government of Kediri Regency, East Java, especially the Regional Apparatus Organizations. Three Regional Apparatus Organizations are the Regional Personnel Agency, the Department of Transportation, and the Region Financial and Asset Management Agency, with a sample of 117 civil servants. The analytical method used is a causal study. Data were analyzed and processed using PLS-SEM statistical programming to evaluate the outer and inner structure of the model. The results reveal that perceived external prestige negatively and significantly affects deviant workplace behavior. The results of the mediation test show that job satisfaction and organizational commitment partially mediate the effect of perceived external prestige on deviant workplace behavior. Subsequent research studies will yield different results in another industry or region. Further research can conduct thorough research on all Regional Apparatus Organizations to obtain comprehensive research results, and systematic sampling techniques can be used to avoid cognitive bias from respondents.